The Role of Audiovisual Speech in the Early Stages of Lexical Processing as Revealed by the ERP Word Repetition Effect. (9th October 2017) - Basirat, Anahita; Brunellière, Angèle; Hartsuiker, Robert
Abstract: Numerous studies suggest that audiovisual speech influences lexical processing. However, it is not clear which stages of lexical processing are modulated by audiovisual speech. In this study, we examined the time course of the access to word representations in long‐term memory when they were presented in auditory‐only and audiovisual modalities. We exploited the effect of the prior access to a word on the subsequent access to that word known as the word repetition effect. Using event‐related potentials, we identified an early time window at about 200 milliseconds and a late time window starting at about 400 milliseconds related to the word repetition effect. Our results showed that the word repetition effect over the early time window was modulated by the speech modality while this influence of speech modality was not found over the late time window. Visual cues thus play a role in the early stages of lexical processing.